Relationships of Serum Bone Turnover Markers With Metabolic Syndrome Components and Carotid Atherosclerosis in Patients With Type 2 Diabetes Mellitus - Li, Wei; Liu, Xiaojun; Liu, Lijun; Zhang, Lei; Li, Mengdi; Liu, Rui; Li, Tianfang; Chen, En; Liu, Shengyun (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to investigate the association of serum bone turnover markers (BTMs) with metabolic syndrome components and carotid atherosclerosis in patients with type 2 diabetes mellitus (T2DM). Methods: We performed a cross-sectional based study in T2DM populations. Serum BTMs including N-terminal osteocalcin (N-MID), β-cross-linked C-telopeptide of type I collagen (β-CTX), and procollagen type I N-terminal propeptide (PINP) were measured by immunoassay method. Carotid artery intima-media thickness and carotid artery plaque (CAP) were measured by B-mode ultrasound. Results: The serum N-MID, PINP, and β-CTX levels significantly decreased in the CAP group compared with the non-CAP group. N-MID and PINP levels were inversely associated with fasting blood glucose, HOMA-IR, CRP, eGFR, and triglycerides (all P < 0.05), whereas β-CTX levels were negatively associated with triglycerides (P < 0.05). After multiple adjustment, the odds ratios (ORs) were substantially higher for CAP with decreased N-MID level (OR = 0.958; 95% CI = 0.926–0.991; P = 0.013). However, serum levels of PINP and β-CTX were not associated with the presence of CAP. Multivariate logistic regression analysis further revealed that serum N-MID, PINP, and β-CTX levels were significantly associated with hypertriglyceridemia, whereas serum N-MID and β-CTX levels were associated with overweight/obesity risk. Conclusions: These findings indicated that serum N-MID level was an independent risk factor for carotid atherosclerosis, whereas BTM levels was associated with other metabolic syndrome components in a T2DM population.